2011
DOI: 10.1179/174367510x12722693956310
|View full text |Cite
|
Sign up to set email alerts
|

TEM investigation of hot pressed ‐10 vol.%SiC–ZrB2composite

Abstract: The polytypism of SiC, phase transformation of ZrB 2 and the interfaces between SiC and ZrB 2 were investigated using high resolution TEM in a hot pressed 10 vol.%SiC-ZrB 2 composite. In most cases, no grain boundary interphases between hexagonal ZrB 2 and 6H-SiC phases were observed with SiC being both inter-and intragranular. Occasionally, 6H-SiC transformed into 3C and 15R and hexagonal ZrB 2 transformed into cubic ZrB. High resolution TEM showed no grain boundary interphases in most regions. Energy dispers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 53 publications
1
27
0
Order By: Relevance
“…A qualitative assessment of ZrB 2 and ZrB 2 -SiC grain boundaries, from the EBSD-OIM data, reveals > 95% are high angle random boundaries, suggesting high mobility. In a similar composite, Jasalyeane et al [45] found predominantly non-coherent unlike interfaces, adding further support to our data. The ratio of Z-Z to Z-S boundaries is close to unity, while the SiC grain boundaries are <10% of all grain boundaries, suggesting minimal influence from the SiC-SiC interfaces.…”
Section: Grain Boundary Slidingsupporting
confidence: 88%
“…A qualitative assessment of ZrB 2 and ZrB 2 -SiC grain boundaries, from the EBSD-OIM data, reveals > 95% are high angle random boundaries, suggesting high mobility. In a similar composite, Jasalyeane et al [45] found predominantly non-coherent unlike interfaces, adding further support to our data. The ratio of Z-Z to Z-S boundaries is close to unity, while the SiC grain boundaries are <10% of all grain boundaries, suggesting minimal influence from the SiC-SiC interfaces.…”
Section: Grain Boundary Slidingsupporting
confidence: 88%
“…Meanwhile, a large sum of ZrC has been produced. And the possible reactions are listed as reaction (3) and (11). H of reaction (7) might be introduced in milling process.…”
Section: Resultsmentioning
confidence: 99%
“…[7,8] Whereas, the densification of ZrB 2 ceramics is a difficult task due to their poor sinterability. [9] Previous works have indicated that ZrB 2 -based ceramics, containing a second phase such as SiC [7,[10][11][12] and ZrC [10], exhibit improved densification behavior and material properties, compared to the corresponding monolithic ceramics. Besides, some other efforts have been made to solve this issue, like effective densification approaches: hot pressing (HP) [4,[13][14][15][16], pressureless sintering (PLS) [7,14,17,18], spark plasma sintering (SPS) [14,[19][20][21][22], reactive processing [23][24][25] and so on.…”
Section: Introductionmentioning
confidence: 98%
“…No grain boundary interphases were detected in most regions but energy dispersive spectroscopy as well as electron energy-loss spectroscopy analyses verified the presence of oxide impurities in the sample [16].…”
Section: Introductionmentioning
confidence: 90%